Structured Speech Acts of Pre-Service EFL Teachers in Indonesia: Interlanguage Pragmatics - Kamarudin Kamarudin (Cordova Journal : languages and culture studies, 2020)
The fascinations that the study of speech acts holds for language teachers, researchers, and practitioners from severe problems to which language use fail to maintain amid the speakers’ communication are imperative to be investigated. This study examines structured speech acts use in terms of its kinds, functions, and how it is performed by pre-service EFL teachers in Indonesia. The theory of Austin’s and Searle’s speech acts were employed as the main reference. This study was a descriptive qualitative method. Content analysis was employed to uncover the description of the research phenomena which in the forms of words, clauses, phrases, and sentences. There were three students in one of the private universities in Lombok, NTB, Indonesia were taken as the respondents. There were twenty-four fragments being analyzed. As the result, the locutionary acts was performed 224 times, then followed by illocutionary acts 223 times, and perlocutionary acts 215 times. Representative function of speech acts was performed 163 times, directive 28 times, expressive 26 times, commissive 6 times, and declarative 0 times. The declarative sentence was highly performed 131 times by the speakers designated the way the speech was acts performed by the speakers.